A Water‐Processable and Bioactive Multivalent Graphene Nanoink for Highly Flexible Bioelectronic Films and Nanofibers. Issue 5 (11th December 2017) - Cheng, Chong; Zhang, Jianguang; Li, Shuang; Xia, Yi; Nie, Chuanxiong; Shi, Zhenqiang; Cuellar‐Camacho, Jose Luis; Ma, Nan; Haag, Rainer
Abstract: The capabilities of conductive nanomaterials to be produced in liquid form with well‐defined chemical, physical, and biological properties are highly important for the construction of next‐generation flexible bioelectronic devices. Although functional graphene nanomaterials can serve as attractive liquid nanoink platforms for the fabrication of bioelectronics, scalable synthesis of graphene nanoink with an integration of high colloidal stability, water processability, electrochemical activity, and especially bioactivity remains a major challenge. Here, a facile and scalable synthesis of supramolecular‐functionalized multivalent graphene nanoink (mGN‐ink) via [2+1] nitrene cycloaddition is reported. The mGN‐ink unambiguously displays a well‐defined and flat 2D morphology and shows good water processability and bioactivity. The uniquely chemical, physical, and biological properties of mGN‐ink endow the constructed bioelectronic films and nanofibers with high flexibility and durability, suitable conductivity and electrochemical activity, and most importantly, good cellular compatibility and a highly efficient control of stem‐cell spreading and orientation. Overall, for the first time, a water‐processable and bioactive mGN‐ink is developed for the design of flexible and electrochemically active bioelectronic composites and devices, which not only presents manifold possibilities for electronic‐cellular applications but also establishes a new pathway for adapting macroscopic usages of graphene nanomaterials in bionic, biomedical, electronic, and even energy fields. Abstract : A water‐processable and bioactive multivalent graphene nanoink (mGN‐ink) featured with well‐defined 2D flat morphology is synthesized. The uniquely chemical, physical, and biological properties of the mGN‐ink endow constructed bioelectronic films and nanofibers with high flexibility and durability, suitable conductivity and electrochemical activity, and most importantly, good electronic‐cellular compatibility and high efficiency in controlling stem‐cell spreading and orientation.